2019
DOI: 10.1029/2019gl083899
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence for Multiple‐Harmonic Standing Alfvén Waves in Jupiter's Equatorial Plasma Sheet

Abstract: Quasiperiodic pulsations in the ultralow‐frequency band are ubiquitously observed in the Jovian magnetosphere, but their source and distribution have until now been a mystery. Standing Alfvén waves on magnetic field lines have been proposed to explain these pulsations and their large range in observed periods. However, in situ evidence in support of this mechanism has been scarce. Here we use magnetometer data from the Galileo spacecraft to report first evidence of a multiple‐harmonic ultralow‐frequency event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…The results presented here represent the first model of ULF wave propagation in the Jovian magnetosphere based on realistic magnetic field and plasma parameters. Our conclusions support and extend the suggestions of Nichols et al (2017), Manners et al (2018), and Manners and Masters (2019) that resonant Alfvén waves can result in the quasiperiodic oscillations in the 10–40 min range. Our model, based on the magnetic field model of Connerney et al (1981) and the plasma model of Bagenal and Delamere (2011), shows a rich spectrum of wave modes in this range.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results presented here represent the first model of ULF wave propagation in the Jovian magnetosphere based on realistic magnetic field and plasma parameters. Our conclusions support and extend the suggestions of Nichols et al (2017), Manners et al (2018), and Manners and Masters (2019) that resonant Alfvén waves can result in the quasiperiodic oscillations in the 10–40 min range. Our model, based on the magnetic field model of Connerney et al (1981) and the plasma model of Bagenal and Delamere (2011), shows a rich spectrum of wave modes in this range.…”
Section: Discussionsupporting
confidence: 92%
“…In situ observations at Jupiter have indicated that magnetic fluctuations in the 10–20 min range were present in Voyager 2 data (Khurana & Kivelson, 1989). Similar observations were made by Galileo (Manners & Masters, 2019; Manners et al, 2018; Wilson & Dougherty, 2000). In addition, Alfvén waves have long been associated with the coupling of the moon Io with the ionosphere of Jupiter (e.g., Acuña et al, 1981; Bagenal, 1983; Belcher et al, 1981; Chust et al, 2005; Crary, 1997; Goertz, 1980; Gurnett & Goertz, 1981; Hinton et al, 2019; Neubauer, 1980); however, the focus of this letter will be on the main auroral oval.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, if this periodicity originated in the solar wind, it is unclear how it would be preserved traveling across Jupiter's bow shock and magnetosheath. Another explanation could involve ultralow frequency (ULF) waves that have been measured to have periods of ∼10 min (Dunn et al, , ; Khurana & Kivelson, ; Manners et al, ; Manners & Masters, ). The frequencies of ULF waves depend on the length and the mass content of the perturbed field line.…”
Section: Discussionmentioning
confidence: 99%
“…The magnetosphere can therefore be treated as an infinite set of independent resonators, each with its own natural frequency and so its own set of harmonics (Wright & Mann, 2013). A case study by Manners and Masters (2019) presented a multiple-harmonic SAW confined to the plasma sheet in the Jovian magnetotail, with spectral properties consistent with frequently observed QPO periods. This demonstrates that at least a subset of QPOs is described by SAWs.…”
Section: Introductionmentioning
confidence: 88%